2021
DOI: 10.1002/jmv.27049
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns in US patients hospitalized with COVID‐19 and pulmonary involvement

Abstract: This study describes the baseline characteristics and treatment patterns of US patients hospitalized with a diagnosis of coronavirus disease 2019 (COVID‐19) and pulmonary involvement. Patients hospitalized with pulmonary involvement due to COVID‐19 (first hospitalization) were identified in the IBM Explorys® electronic health records database. Demographics, baseline clinical characteristics, and in‐hospital medications were assessed. For evaluation of in‐hospital medications, results were stratified by race, g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
(24 reference statements)
7
13
0
Order By: Relevance
“…In general, most of the findings of this report regarding sociodemographic data, comorbidities and pharmacological treatment were consistent with what has been described in other studies carried out in the world [13][14][15][16][17][18][19][20][21][22]. The median age was similar to that found in other studies (55.0-60.0 years) [13,14,23] and lower than that reported by others (50.4-68.1 years) [19][20][21][22]24], with a predominance of men, as identified in the majority of studies [13,14,20,[22][23][24][25][26], which may be due to biological factors such as genes, sex hormones and microbiome that may influence the host immune responses to infections [27]; though some reports have had a higher proportion of women (51.2-64.6%) [15,16,28]. The most frequently found comorbidities were arterial hypertension, diabetes mellitus, and chronic obstructive pulmonary disease, in line with other studies [13,14,[20][21][22][23][24]29].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In general, most of the findings of this report regarding sociodemographic data, comorbidities and pharmacological treatment were consistent with what has been described in other studies carried out in the world [13][14][15][16][17][18][19][20][21][22]. The median age was similar to that found in other studies (55.0-60.0 years) [13,14,23] and lower than that reported by others (50.4-68.1 years) [19][20][21][22]24], with a predominance of men, as identified in the majority of studies [13,14,20,[22][23][24][25][26], which may be due to biological factors such as genes, sex hormones and microbiome that may influence the host immune responses to infections [27]; though some reports have had a higher proportion of women (51.2-64.6%) [15,16,28]. The most frequently found comorbidities were arterial hypertension, diabetes mellitus, and chronic obstructive pulmonary disease, in line with other studies [13,14,[20][21][22][23][24]29].…”
Section: Discussionsupporting
confidence: 91%
“…The median age was similar to that found in other studies (55.0-60.0 years) [13,14,23] and lower than that reported by others (50.4-68.1 years) [19][20][21][22]24], with a predominance of men, as identified in the majority of studies [13,14,20,[22][23][24][25][26], which may be due to biological factors such as genes, sex hormones and microbiome that may influence the host immune responses to infections [27]; though some reports have had a higher proportion of women (51.2-64.6%) [15,16,28]. The most frequently found comorbidities were arterial hypertension, diabetes mellitus, and chronic obstructive pulmonary disease, in line with other studies [13,14,[20][21][22][23][24]29]. These are pathologies that have been associated with a greater probability of presenting complications, severe forms of the disease and death [30,31].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Further investigations are required to fully understand the reasons for the disparities in index treatment use by patient age, gender, race, region, and comorbidity profile identified in this study, and their effects on patient outcomes. Treatment may have been guided by various patient-level and healthcare system-level factors, including disease severity, differences in practice protocols, and the availability of medications and healthcare resources [ 7 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few real-world studies examining COVID-19 treatment patterns among patients hospitalized with COVID-19 have been published [ 7 , 25 , 27 , 32 ]. To the authors’ knowledge, no other studies have reported on longitudinal treatment patterns for patients hospitalized with COVID-19.…”
Section: Discussionmentioning
confidence: 99%